Glutathione amide and its perthiol in anaerobic sulfur bacteria. - Bartsch, R G (1996)
Chromatium species produced the novel biological thiol glutathione amide, gamma-L-glutamyl-L-cysteinylglycine amide (GASH), when grown photoheterotrophically. GASH was largely converted to the corresponding perthiol during photoautotrophic growth on sulfide, suggesting that GASH may have a function in anaerobic sulfide metabolism. This unprecedented form of glutathione metabolism was probably present in anaerobic ancestors of modern cyanobacteria and purple bacteria.